Government guarantees and bank liquidity creation around the world - Berger, Allen N.; Li, Xinming; Saheruddin, Herman; Zhao, Daxuan (Journal of Banking & Finance, 2024)
Governments provide bank guarantees, such as deposit insurance. While risk effects are well researched, impacts on bank output remain largely unexplored. We investigate bank output effects using data from 75 countries/regions on bank liquidity creation, a comprehensive bank output measure. We address reverse causality, examining home-country guarantee effects on liquidity creation by subsidiary banks in foreign host nations, and mitigate omitted-variables concerns with host country × year fixed effects and home country controls. Findings suggest home-country guarantees decrease subsidiary bank liquidity creation up to 10%, and hold prior to, during, and after the Global Financial Crisis.